Rancang Bangun Purwarupa Mobil Bergerak Menggunakan Pengendali Suara Berbasis Mikrokontroler Atmega328 - Serli Yuni Wulandari; Joko Saputro; Asruddin Asruddin (FIKOM Universitas Bung Karno, 2023)
One type of prototype car with interesting special abilities to develop is a voice-controlled prototype car based on the ATmega328 microcontroller module EasyVR, Motor Driver as the stepper motor controller, and using wheels with a stepper motor as the driver. EasyVR Commander serves as the voice recorder. In the control system, several voice commands are used. The first command is